Evaluasi Strategi Peningkatan Daya Saing Usaha Mikro di Sektor Kuliner melalui Implementasi Modul CRM pada Sistem ERP Open Source Odoo - Novia Andini; Haerul Haerul; Win Ce; Yudi Ramdhani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Micro-enterprises play a crucial role in driving Indonesia’s national economic growth. To survive in an increasingly competitive environment and continue to develop, the adoption of technology has become an unavoidable necessity for business actors. This study aims to analyze the effectiveness of implementing the Customer Relationship Management (CRM) module within the Odoo Enterprise Resource Planning (ERP) system in supporting strategies to enhance the competitiveness of micro-enterprises. The research employs the Prototype method, which includes stages of requirements gathering, system design and configuration, implementation, User Acceptance Testing (UAT), as well as system deployment and strategic evaluation. The results indicate that the implementation of the CRM module provides measurable positive impacts on operational performance and customer relationship management. The frequency of recorded customer interactions increased from an average of 3 to 10 interactions per day, the number of new customers rose from 5 to 12 customers per week, and the number of repeat customers increased from 8 to 18 customers per week. In terms of operational efficiency, the time required for transaction recording was reduced from approximately 10 minutes to 4 minutes per transaction through process automation within the ERP system. In addition, access to data and reports that was previously manual and unstructured is now available automatically and in real time, thereby supporting faster and data-driven decision-making by business owners.Strategically, the implementation of ERP through the CRM module has proven to be an effective tool in strengthening the competitive position of micro-enterprises. This is reflected in improved quality of customer interactions, increased acquisition of new customers, and growing customer loyalty. These improvements were achieved through the optimal utilization of features available in the Odoo system, enabling the CRM module to be maximized in supporting the sustainability and development of micro-enterprises.